An examination of energy efficiency retrofit depth in Ireland - Matthew Collins; John A. Curtis (The Economic and Social Research Institute (ESRI), 2016)
This study examines energy efficiency retrofit depth in Ireland using data from a national residential grant scheme for energy efficiency upgrades. We specifically examine both the number of retrofit measures adopted per dwelling, and also the comprehensiveness of retrofits upgrades, which are retrofits in excess of the most common and simple retrofit combinations. We find that certain obligated parties, who are obliged by the State to reduce energy consumption in Ireland, vary both positively and negatively in terms of number of retrofit measures relative to private retrofits, but perform negatively with regard to comprehensive retrofits. All parties are found to perform negatively with regard to comprehensive retrofits, relative to private applications. Newer homes, relative to older homes are more likely to invest in more retrofit measures but less likely to engage in more comprehensive retrofits. Regionally, homes in the Greater Dublin Area are less likely to undertake more retrofit measures but more likely to engage in more comprehensive retrofits, while the opposite is true of rural areas. A seasonal trend also exists, with applications made during autumn and winter much less likely to be made for more comprehensive retrofits. Demand for more measures and more comprehensive retrofits does not appear to be affected by financial incentives as the introduction of a bonus for three- and four-measure retrofits has not coincided with any increases in the demand for such retrofits.
Keywords: 330; energy efficiency; energy retrofits; retrofit intensity; truncated count data estimation